High time resolution fluctuations in volcanic carbon dioxide degassing from Mount Etna - Pering, T.D.; Tamburello, G.; McGonigle, A.J.S.; Aiuppa, A.; Cannata, A.; Giudice, G.; Patanè, D. (Journal of volcanology and geothermal research, 2014)
We report here on the first record of carbon dioxide gas emission rates from a volcano, captured at ≈1Hz. These data were acquired with a novel technique, based on the integration of UV camera observations (to measure SO2 emission rates) and field portable gas analyser readings of plume CO2/SO2 ratios. Our measurements were performedat the North East crater of Mount Etna, southern Italy, and the data reveal strong variability in CO2 emissions over timescales of tens to hundreds of seconds, spanning two orders of magnitude. This carries importantimplications for attempts to constrain global volcanic CO2 release to the atmosphere, and will lead to an increased insight into short term CO2 degassing trends. A common oscillation in CO2 and SO2 emission rates in addition to the CO2/SO2 ratios was observed at periods of ≈89s. Our results are furthermore suggestive of an intriguing temporal lag between oscillations in CO2 emissions and seismicity at periods of ≈300–400s, with peaks and troughs in the former series leading those in the latter by ≈150s. This work opens the way to the acquisition of further datasets with this methodology across a range of basaltic systems to better our understandingof deep magmatic processes and of degassing links to manifest geophysical signals. •A new methodology has been developed to capture high time resolution carbon dioxide flux.•Volcanic carbon dioxide emissions vary rapidly at short timescales.•Emission of carbon dioxide and sulphur dioxide are linked by a common periodicity.•Our results demonstrate an intriguing link between gas flux and seismicity.